Orbital forcing of ice sheets during snowball Earth - Ross N. Mitchell; Thomas M. Gernon; Grant M. Cox; Adam R. Nordsvan; Uwe Kirscher; Chuang Xuan; Yebo Liu; Xu Liu; Xiaofang He (Nature Communications, 2021)
Reconciling the Snowball Earth hypothesis with sedimentological cyclicity has been a persistent challenge. A new cyclostratigraphic climate record for a Cryogenian banded iron formation in Australia provides evidence for orbital forcing of ice sheet advance and retreat cycles during Snowball Earth.